Environmental Benefits of Conservation Agriculture - Pramanik, P.; Sharma, D. K.; Maity, A. (Indian Farming, 2015)
Conservation farming systems are dynamic and call for continual learning and improvement. Well managed grazing, weed, insect and fertiliser programs are required for successful conservation farming and it takes time and experience to develop these skills. A good understanding of the interaction between plants, the soil system and the environment is necessary. Conservation farming systems need to be flexible and responsive and to work within the constraints and opportunities of the environment and not against it.